Transmission Electron Microscopic Morphological Study and Flow Cytometric Viability Assessment of Acinetobacter baumannii Susceptible to Musca domestica cecropin - Shuiqing Gui; Rongjiang Li; Yongwen Feng; Sanming Wang (The Scientific World Journal)
Multidrug-resistant (MDR) Acinetobacter baumannii infections are difficult to treat owing to the extremely limited armamentarium. Expectations about antimicrobial peptides' use as new powerful antibacterial agents have been raised on the basis of their unique mechanism of action. Musca domestica cecropin (Mdc), a novel antimicrobial peptide from the larvae of Housefly (Musca domestica), has potently active against Gram-positive and Gram-negative bacteria standard strain. Here we evaluated the antibacterial activity of Mdc against clinical isolates of MDR-A. baumannii and elucidate the related antibacterial mechanisms. The minimal inhibitory concentration (MIC) of Mdc was 4 μg/mL. Bactericidal kinetics of Mdc revealed rapid killing of A. baumannii (30 min). Flow cytometry using viability stain demonstrated that Mdc causes A. baumannii membrane permeabilization in a concentration- and time-dependent process, which correlates with the bactericidal action. Moreover, transmission electron microscopic (TEM) examination showed that Mdc is capable of disrupting the membrane of bacterial cells, resulting in efflux of essential cytoplasmic components. Overall, Mdc could be a promising antibacterial agent for MDR-A. baumannii infections.